Determinant of Student Decisions in Choosing Diploma Study Program at Vocational College - Amir Hamzah; Tito Prayitno (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
The requirements in entering the world of work today demand professional skills and abilities according to the needs of the organization. Therefore, effective marketing strategies become important for vocational colleges to get prospective students. There are several studies that examine the factors that influence students' decisions in choosing a college, but research focusing on vocational college research is still very limited. This study aims to analyze the determinants that influence students' decisions in choosing a course of study at a Vocational College. This study was conducted by an online survey of 158 respondents who were studying at three Vocational Universities in Banten Province, namely ASM Lepisi, Politeknik LP3I Jakarta Tangerang Campus, and Politeknik PGRI Banten. Analyze the data using Partial Least Square Structural Equation Modeling (PLS-SEM). Finally, the author expects the empirical results of this study to be useful as a reference for marketing practitioners of Vocational Universities in West Java and Banten, in particular and Indonesia in general.